Reduced-tillage and Crop Productivity in Indian Arid Zone - Mohanram, Saritha; Kumar, Praveen; Panwar, Nav Raten; Burman, Uday (Annals of Arid Zone, 2022)
The increasing costs of energy, equipment, labor and the growing concern over soil loss have paved the way to development of reduced-tillage systems in place of conventional tillage. These residue-retaining reduced-tillage systems are especially effective in controlling soil erosion and substantially enhancing soil water storage. This modification of the soil microclimate by reduced-tillage exerts beneficial effects on the soil microbial communities which plays a great role in nutrient transformations. While minimum tillage allows for minimal soil disturbance during field operations, no-tillage refers to the complete absence of tillage. In practice, if one desires to reap equal or higher yields and better environmental performance with minimum tillage than with conventional tillage systems, several components need to be applied to a conservation agriculture system. This can lead to variable yield responses with the minimum-/ no-till management system, especially in a rainfed agro-ecology. Here we review the suitability of reduced-tillage in arid regions, especially with reference to India where experiments on minimum tillage started in the early eighties. The results show limited success with this concept in Indian arid region, where climate and residue availability are a matter of concern. So, successful implementation of reduced-tillage systems as a potential solution to sustainable agricultural intensification needs 1) better understanding of crop and environmental variables and 2) appropriate adoption measures with ample institutional and technology support, over a long term.